Effect of Pro.Sol and Folicist on some vegetative growth Characters of Olive transplants (Olea europaea L.) cvs. Sorany and Picual (a) - Mayi, Azad A.; Gulala (Sulaimani Journal for Pure and Applied Sciences, 2015)
This study was carried out during the growing season (2014) in Bakrajo Nursery Station/ Sulaimani, Kurdistan Region-Iraq. Uniform and healthy olive Olea europaea L.) cvs. Sorany and Picual transplants of (2) years old were used. Transplants were grown in pots each of (5 kg) weight, to investigate the effect of three Folicist concentrations (0, 60 and 120 mg.L-1, three concentrations of Pro-Sol (0,100 and 200mg.L-1) and their interactions on vegetative growth of Olive cvs. Sorany and Picual transplants. The results showed that as follow: Foliar sprays of Folicist significantly dominated over Pro.Sol at all vegetative growth characters, except plant height, lateral shoot lengths. Picual cv. significantly dominated over cv. Sorany at all vegetative growth characters, except laterals future fertilization requirements, shoot length and leaf number/shoot. The interactions between Pro-Sol, Folicist and cv. Sorany affected significantly on most of the vegetative growth characteriste. While, Pro.Sol, Folicist and cv. Picual interaction increased stem diameter.
Keywords: ProSol; Folicist; Olive cultivar; Vegetative growth characters